Terpenoids from Dacrycarpus imbricatus. - Hau, Dang Viet; Tam, Nguyen Thanh; Hoang Anh, Nguyen Thi; Quan, Tran Duc; Thien, Dao Duc; Hong Nhun, Le Thi; Tinh, Bui Xuan; Tuan, Nguyen Le; Loc, Tran Van; Sung, Tran Van; et al. (Vietnam Journal of Chemistry, 2017)
The phytochemical investigation of the hexane extract from the twigs and leaves of Dacrycarpus imbricatus (Blume) de Laub led to the isolation of a rare sesquiterpene, spathulenol (1) along with three diterpenes named pimaric acid (2), trans-communic acid (3) and cis-communic acid (4). Their structures were determined by combination of spectral analysis and comparison with reported data. This is the first report on isolation of compound 1 from the Podocarpaceae family. Keywords. Dacrycarpus imbricatus, spathulenol, pimaric acid, communic acid.